Pengaruh Foreign Direct Investment (FDI), Keterbukaan Perdagangan Dan Inflasi Terhadap Pertumbuhan Ekonomi Di 5 Negara ASEAN Pada Tahun 2014 – 2023 Dalam Perspektif Ekonomi Islam - Kurniawan, Muhammad; Komala Sari; Zathu Restie Utamie (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aims to examine the influence of Foreign Direct Investment (FDI), Trade Openness, and Inflation on Economic Growth (GDP). The data used in this research was taken from the World Bank, covering a sample of 5 countries in ASEAN during the period 2014 to 2023 which met the research criteria. The type of data used is secondary data, and the analysis is carried out using panel data regression techniques, which are a combination of time series and cross section data. The research results show that the Foreign Direct Investment (FDI) variable has a significant and positive effect on Economic Growth. On the other hand, the Trade Openness and Inflation variables do not show a significant effect, with a negative direction on economic growth. The coefficient of determination value shows that the combined influence of Foreign Direct Investment (FDI), Trade Openness and Inflation on Economic Growth reaches 27.1453%, while the rest can be explained by other variables. To encourage economic growth in the 5 ASEAN countries, it is recommended that the government increase capital flows from foreign investment (FDI). Apart from that, it is important for the government to maintain stability in Export Import and inflation to support sustainable economic growth.